Persepsi Guru dan Siswa Terhadap Integrasi Kecerdasan Buatan Dalam Pembelajaran Biologi: Eksplorasi Peluang dan Tantangan - Damasus Nosi Resi; Sutarno Sutarno; Meti Indrowati (Universitas Sebelas Maret, 2025)
Artificial intelligence (AI) has become a new educational space and an integral part of the rapid development of education and technology in today's modern era. However, the use of AI faces various problems and obstacles, including in biology education, which has been exposed to the effects of AI as a current learning mechanism. The purpose of this study is to explore and investigate teachers' and students' perspectives on the integration of AI in biology education and to understand its opportunities and challenges. This study adopts a qualitative method, conducting a survey administered to biology teachers and three classes under their supervision (n = 96 students) at one high school in Surakarta. The analysis instrument, in the form of a questionnaire designed with applied questions, was used as an evaluation framework to analyze teachers' and students' perspectives on the integration of AI in biology education. The research findings revealed that teachers and students share similar perspectives on the opportunities and challenges of utilizing AI in biology education. This finding identified opportunities such as effectiveness, time efficiency, and personalized learning as the main factors enabling the adoption of AI in biology education. The study also addressed various challenges faced, including ethical issues related to AI use, the decline in critical thinking skills due to overreliance on AI among students, and the limited AI literacy skills among teachers. The study emphasizes the importance of accommodative activities such as socialization and training in the use of artificial intelligence in biology education as a synergistic effort to foster a positive attitude in preparing teachers and students to adapt and innovate in the era of AI transformation.